Study of the mechanical and thermodynamic properties of some MAX phase compounds using computational methods - Douidi ali aboubakeur Enc/ Saber Saad Essaoud (UNIVERSITE MOHAMED BOUDIAF - M’SILA, 2025)
In this work, we carried out a theoretical study to investigate the structural, electronic, elastic, and thermodynamic properties of the compounds V2SnC and V2SnN using the GGA-PBEsol approximation within the framework of Density Functional Theory (DFT). For the structural properties, we calculated the lattice constants, bulk modulus, and its first pressure derivative. To understand the electronic behavior of both compounds, we analyzed the electronic band structure and the total and partial density of states (DOS). Subsequently, the elastic properties were evaluated by calculating the fundamental elastic constants, along with derived parameters such as the shear modulus, Young’s modulus, and Poisson’s ratio. Finally, the thermodynamic properties were studied, including heat capacity, entropy, thermal expansion coefficient, Debye temperature, and bulk modulus under varying temperature and pressure conditions.